2018
DOI: 10.1002/cbf.3370
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rheumatoid arthritis (RA) and osteoarthritis (OA) based on microarray profiles of human joint fibroblast‐like synoviocytes

Abstract: The purpose of the present study was to investigate the underlying molecular mechanism of osteoarthritis (OA) and rheumatoid arthritis (RA) based on microarray profiles. Three human joint fibroblast-like synoviocytes (FLSs) microarray profiles including 26 OA samples, 33 RA samples, and 20 healthy control (HC) samples were downloaded from the GEO database. Differentially expressed genes (DEGs) between OA and HC (DEGsOA) and RA and HC (DEGsRA) were identified. Co-expressed and specific genes were analysed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 63 publications
3
37
0
Order By: Relevance
“…The top 10 enriched pathways (ranged by Count) are shown in Figure a. As expected, the top three pathways (cytokine receptor interaction, chemokine signaling pathway, and cell adhesion molecular [CAMs]) all indicated that the interaction between cytokines/chemokines and their receptor on plasma membrane might be the main pathogenesis of RA (Cai et al, ; Mori et al, ), consistent with the results of GO analysis (Figure c). In the PPI network of DEGs, the top 5 hub genes including CD44, C‐X‐C motif chemokine ligand 10 (CXCL10), SDC4, guanylate binding protein 1 (GBP1), and MMP1 were identified (Figure b).…”
Section: Resultssupporting
confidence: 82%
“…The top 10 enriched pathways (ranged by Count) are shown in Figure a. As expected, the top three pathways (cytokine receptor interaction, chemokine signaling pathway, and cell adhesion molecular [CAMs]) all indicated that the interaction between cytokines/chemokines and their receptor on plasma membrane might be the main pathogenesis of RA (Cai et al, ; Mori et al, ), consistent with the results of GO analysis (Figure c). In the PPI network of DEGs, the top 5 hub genes including CD44, C‐X‐C motif chemokine ligand 10 (CXCL10), SDC4, guanylate binding protein 1 (GBP1), and MMP1 were identified (Figure b).…”
Section: Resultssupporting
confidence: 82%
“…DEGs were identified by the inclusion criteria with P value < 0.05 and fold change (FC) ≥ 2 [ 25 ]. The visualization of DEGs was drawn via volcano plot and Venn diagram by using the ggplot2 and VennDiagram packages in R language (version 3.5.1) ( http://www.r-project.org/ ) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…DEGs were identi ed by the inclusion criteria with P. value <0.05 and fold change (FC) ≥ 2 [25]. The visualization of DEGs was drawn via volcano plot and venn diagram by using the ggplot2 and VennDiagram packages in R language (version 3.5.1) (http://www.r-project.org/) [26].…”
Section: Screening Of Differential Expression Genes (Degs)mentioning
confidence: 99%